Perception and Impact of Coffee Consumption Patterns on the Risk of Gastritis in Generation Z at the Nurse Station of Grandmed Hospital Lubuk Pakam - Anita Sri Gandaria Purba; Dian Anggri Yanti; Rahmat Ali Putra Harahap; Khairunnisa Batubara; Icha Tirani Vira (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
The habit of consuming coffee can be one of the triggers for gastritis, because the caffeine content in it can stimulate increased production of stomach acid. This causes excess gas to accumulate in the stomach, which often causes complaints such as bloating, nausea, and pain in the pit of the stomach. Individuals who regularly consume coffee are at greater risk of suffering from gastritis than those who do not consume it. This research will analyze the perception and impact of coffee consumption patterns on gastritis in Generation Z at Nurse Station 2D, Grandmed Hospital, Lubuk Pakam. The method used is quantitative research with a Cross-Sectional Study design. The study population was patients in the Inpatient Room 2D of Grandmed Hospital, where the sample was selected using purposive sampling. The results of the Chi-Square test showed a p value of 0.003, which means that there is a relationship between coffee consumption patterns and the risk of gastritis in patients in the Inpatient Room 2D, Grandmed Hospital, Lubuk Pakam.